KONSEP PENERAPAN MEDIASI PENAL DALAM PENYELESAIAN TINDAK PIDANA RINGAN PERSPEKTIF RESTORATIVE JUSTICE - TITIN APRIANI; SYAIFULLAH SYAIFULLAH; MUHAMMAD IKBAL (Universitas Mahasaraswati K. Mataram, 2021)
The purpose of this study is to determine the concept of applying penal mediation in the resolution of minor crimes from a restorative justice perspective and to determine the process of resolving minor crimes from a restorative justice perspective. The type of research used is normative research, namely research on legal principles related to the application of penal mediation related to minor crimes in the perspective of Restorative Justice. The approach method used in this research is the statutory approach and the conceptual approach.The results of the study indicate that mediation can be carried out at the prosecution level or at the trial court with considerations of legal certainty, legal benefits and legal justice with the argument that if penal mediation is carried out at the prosecution level, the principle that can be used is the principle of opportunity which is a teaching that gives authority to Prosecutors to set aside the case, even though there is sufficient evidence, in the public interest, either with conditions or without conditions. In a restorative justice approach, all parties, namely the victim, the defendant and other related parties, are involved to jointly seek a fair solution by emphasizing restoration to its original state and not retaliation. By looking at the severity of the Defendant's actions and considering the aspects of the restorative approach and the benefits of the law, as well as for the creation of justice in society, the Judge supports the Peace Agreement that has been made between the Defendant and the victim with the aim that the Defendant can realize his mistakes and improve himself and not repeat the criminal act. at a later time